1995
DOI: 10.1103/physrevlett.74.3860
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Effect on Surface Diffusion: CO/S/Ni(110)

Abstract: Macroscopic CO diffusion on Ni(110) was found to be greatly impeded by surface contamination of just a few percent of a sulfur monolayer. The effect became even much more pronounced if the sample was annealed at high temperatures.The results can be understood from the consideration that S-covered steps can effectively block CO diffusion with a much higher energy barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…[51][52][53][54] We note that surface mobility of hydrogen can decrease by a factor of ϳ60 as the surface carbon coverage was increased from C =0 to C = 0.42 ML at T = 300 K. 52 However, in our case, the amount of impurities was below the AES sensitivity. Comparing our measured diffusion coefficient D with the extrapolated value from QHAS results, we see a difference of more than four orders of magnitude (see Fig.…”
Section: Comparison With Previous Resultsmentioning
confidence: 56%
“…[51][52][53][54] We note that surface mobility of hydrogen can decrease by a factor of ϳ60 as the surface carbon coverage was increased from C =0 to C = 0.42 ML at T = 300 K. 52 However, in our case, the amount of impurities was below the AES sensitivity. Comparing our measured diffusion coefficient D with the extrapolated value from QHAS results, we see a difference of more than four orders of magnitude (see Fig.…”
Section: Comparison With Previous Resultsmentioning
confidence: 56%
“…We have chosen to use sulfur which is a well-known inhibitor or poison to active sites in general 23,27,28 due to its strong interaction with undercoordinated sites. 29,30 In particular for the methanation reaction over ruthenium, Goodman and co-workers have shown that less than 5% of a monolayer of sulfur was needed to poison up to 70% of the methanation activity on a Ru(001) crystal, see ref. [31][32][33] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Since the period of the coverage grating is on the micron scale so it contains many steps, step effects can appear in our measurements if they are important. 13 By aligning the onedimensional adsorbate grating parallel or perpendicular to the steps, diffusion anisotropy can be measured.…”
Section: Introductionmentioning
confidence: 99%